The Role of Monitoring, Prior Knowledge, and Working Memory in University Students’ Expository Text Comprehension - Juan P. Barreyro; Sofía S. Ortíz; Jesica Formoso (Psicología Educativa: Revista de los Psicólogos de la Educación)

(untitled)
The aim of this study is to analyze the impact of a monitoring strategy on the comprehension of expository texts, taking into account the influence of prior knowledge and working memory capacity in university students. Two experiments were conducted. The first investigated whether the use of the monitoring strategy enhanced comprehension of expository texts that required different levels of prior knowledge. The second experiment enquired into the role of working memory in conjunction with the monitoring strategy and varying levels of prior knowledge. The results revealed that the use of the monitoring strategy improved comprehension regardless of prior knowledge level. Furthermore, high working memory capacity is found to be associated with better comprehension, particularly in texts with low prior knowledge content. These findings highlight the importance of considering both the monitoring strategy and working memory capacity in the comprehension of expository texts, with implications for university contexts.